CONSORTIUM OF MULTIFUNCTIONAL MICROORGANISMS IN SOY CULTURE (Colloquium Agrariae. ISSN: 1809-8215, 2023)
The use of multifunctional microorganisms (MM) directly benefits the growth and development of plants because of the production of phytohormones and siderophores, supply of nutrients and assimilation of atmospheric nitrogen (N2); as well as, indirectly, by protecting plants against pathogens. In this way, the search for cultivation technologies that provide productive increments and minimize production costs and negative impacts on the environment is of great importance in the search for sustainable agricultural systems. The objective of this work was to determine the effect of multifunctional microorganisms on gas exchange, grain yield and production components in soybean plants. In the field experiment, 2019/2020 harvest, a randomized block design was used, with 32 replications. Soybean plants were treated with a consortium of microorganisms Serratia marcenses (BRM 32114) + Bacillus spp. (BRM63573) and, as a control, soybean plants treated without intercropping. Soybean plants treated with microorganisms showed an increase in photosynthetic rate (16.65%), stomatal conductance (37.50%), internal concentration of CO2 (10.36%), mass of 100 grains (4.04%) and yield of grains (14.83%) in relation to untreated plants. Therefore, the use of a consortium of multifunctional microorganisms, that is, the combination of multiple functionalities from different microorganisms, shows potential to increase the agronomic performance of soybean plants. The use of co-inoculation technology appears as a strategic component to achieve sustainable agriculture.